Comprehensive analysis of the Caffeic acid O-methyltransferase gene family in kenaf (Hibiscus cannabinus L.) and their expression characteristics in response to salinity stress - Xu, Jiantang; Liu, Tianjin; Lin, Hui; Huang, Rong; Chen, Meixia; Fang, Pingping; Niu, Xiaoping (Frontiers in Plant Science, 2025)
Caffeic acid O-methyltransferase (COMT) catalyzes the penultimate methylation in monolignol biosynthesis, controlling lignin composition and abiotic-stress tolerance. Kenaf (Hibiscus cannabinus L.), a fast bast-fiber crop rich in lignin, is valued for its mechanical strength and resilience to salinity. However, the COMT gene family has not yet been systematically characterized in this species. Here, we integrated phylogenetics, synteny, promoter and transcriptome analyses to create a comprehensive profile of kenaf COMT genes. Genome-wide screening identified 81 HcCOMT genes. Phylogenetic reconstruction with COMTs from Arabidopsis thaliana and Gossypium hirsutum resolved 10 distinct clades. Synteny analysis revealed 2 collinear blocks with Arabidopsis and 14 with cotton, whereas intraspecific duplication events indicated recent lineage-specific expansion. Promoter analysis identified numerous cis-elements responsive to light, phytohormones and abiotic stress, suggesting complex transcriptional regulation. Transcriptome mining uncovered 6 candidate genes with pronounced tissue specificity and salt responsiveness; qRT-PCR confirmed these patterns in root, stem and leaf tissues under 200 mM NaCl: HcCOMT28 and HcCOMT29 were repressed in the leaf, whereas HcCOMT11, HcCOMT12, HcCOMT13, and HcCOMT17 were up-regulated, consistent with altered lignin deposition patterns. Our findings provide a comprehensive genomic resource delineating the structure, evolution, and salt-responsive expression of the kenaf COMT family, and establish a foundation for elucidating the molecular mechanisms underlying lignin-mediated salt tolerance and for breeding elite kenaf cultivars with tailored fiber properties.